Chemical evolution of fluorine in the Milky Way. Issue 1 (4th November 2022) - Womack, Kate A; Vincenzo, Fiorenzo; Gibson, Brad K; Côté, Benoit; Pignatari, Marco; Brinkman, Hannah E; Ventura, Paolo; Karakas, Amanda
ABSTRACT: Fluorine has many different potential sites and channels of production, making narrowing down a dominant site of fluorine production particularly challenging. In this work, we investigate which sources are the dominant contributors to the galactic fluorine by comparing chemical evolution models to observations of fluorine abundances in Milky Way stars covering a metallicity range of −2 < [Fe/H] < 0.4 and upper limits in the range of −3.4 < [Fe/H] < −2.3. In our models, we use a variety of stellar yield sets in order to explore the impact of varying both asymptotic giant branch (AGB) and massive star yields on the chemical evolution of fluorine. In particular, we investigate different prescriptions for initial rotational velocity in massive stars as well as a metallicity-dependent mix of rotational velocities. We find that the observed [F/O] and [F/Fe] abundance ratios at low metallicity and the increasing trend of [F/Ba] at [Fe/H] ≳ −1 can only be reproduced by chemical evolution models assuming, at all metallicities, a contribution from rapidly rotating massive stars with initial rotational velocities as high as 300 km s −1 . A mix of rotational velocities may provide a more physical solution than the sole use of massive stars with v rot = 300 km s −1, which are predicted to overestimate the fluorine and average s-process elemental abundances at [Fe/H] ≳ −1. The contribution from AGB stars is predicted to start at [Fe/H] ≈ −1 and becomes increasingly important at high metallicity, being strictly coupled to the evolution of the nitrogen abundance. Finally, by using modern yield sets, we investigate the fluorine abundances of Wolf–Rayet winds, ruling them out as dominant contributors to the galactic fluorine.